If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x-4)=-(x-7)
We move all terms to the left:
2(x-4)-(-(x-7))=0
We multiply parentheses
2x-(-(x-7))-8=0
We calculate terms in parentheses: -(-(x-7)), so:We get rid of parentheses
-(x-7)
We get rid of parentheses
-x+7
We add all the numbers together, and all the variables
-1x+7
Back to the equation:
-(-1x+7)
2x+1x-7-8=0
We add all the numbers together, and all the variables
3x-15=0
We move all terms containing x to the left, all other terms to the right
3x=15
x=15/3
x=5
| -2(1.6-3)+x=2 | | -2(1.6-3)+x=3 | | B-(0.17b)= | | 2x+15x=51 | | -9x+7=-2x-7 | | y=49+11 | | 0.4-y=-17.6 | | y=15+7 | | m/6+24=27 | | 4.0x+4=2.0x+8 | | x+2x^2+x+20x=0 | | (x+2)(x^2+x+20x)=0 | | h/10+30=35 | | -3(a−4)=-9 | | 4=m-35/9 | | 3^(2x+5)=5^(2x) | | 9+9t=72 | | 90=38.43+0.25x | | w+11/5=7 | | 17.8+n=20 | | 4/15=-2/5a | | 10=p+16/3 | | 99=9(b+7) | | 5x-4+3x+31+4x+15+7x-64+6x-8+153+120=360 | | 9+3g=36 | | (2x+1)=360 | | 3x+7=9x+14 | | (4x+7)=360 | | 15=2n-5 | | 16=-4/5z | | 15=h/4+11 | | 34z=-91.8 |